Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1002/pmic.200401134
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of heat shock protein 27 phosphorylation sites in renal cell carcinoma

Abstract: The phosphorylation of heat shock protein 27 (HSP27) occurs differently in human renal cell carcinoma (RCC) compared to homologous normal kidney tissue. Two-dimensional electrophoresis was used to separate and visualize HSP27, via immunostaining with anti-HSP27 antibody, in tumor and normal renal samples, obtained after surgery resection from patients with RCC. The mean number of protein species was 21 in RCC and 15 in normal tissues. Selected spots were in-gel digested with trypsin, extracted and analyzed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…Previous 2D gel electrophoresis studies of heart tissues and cell lines reported largely diversified results for the number of HSP27 spots. Depending on the cell type, the number of isoforms with different phosphorylation status varied from 2 to 80 (10,42,44,47). Especially in pathogenic tissues, increased numbers of HSP27 spots have been observed in 2D gels, likely because of disintegration of HSP27 oligomers and also different degrees of phosphorylation, such as, for example, mono-, di-, and triphosphorylation.…”
Section: Attenuation Of Dox-induced Apoptosis In Heat-shocked Cardiacmentioning
confidence: 99%
“…Previous 2D gel electrophoresis studies of heart tissues and cell lines reported largely diversified results for the number of HSP27 spots. Depending on the cell type, the number of isoforms with different phosphorylation status varied from 2 to 80 (10,42,44,47). Especially in pathogenic tissues, increased numbers of HSP27 spots have been observed in 2D gels, likely because of disintegration of HSP27 oligomers and also different degrees of phosphorylation, such as, for example, mono-, di-, and triphosphorylation.…”
Section: Attenuation Of Dox-induced Apoptosis In Heat-shocked Cardiacmentioning
confidence: 99%
“…Prominently, three spots were observed in control hearts. These three spots are assigned to nonphosphorylated, monophosphorylated, and diphosphorylated Hsp27 (5,29). In some studies Pro-Q staining (a marker of phosphorylated proteins) has stained all the three spots, and these studies have described this as mono-, di-, and triphosphorylated Hsp27 (8).…”
Section: Discussionmentioning
confidence: 99%
“…4). Based on previous studies of Hsp27, this m/z is for the nonphosphorylated peptide (5,29). Mass difference between COOH terminal containing fragments y6 and y7 as well as y7 and y8 is close to 87 (Fig.…”
Section: Proteomics Of Hsp25 In Dox-treated Failing Heartsmentioning
confidence: 99%
“…AlphaB-crystallin expression has also been demonstrated to varying extent in numerous epithelial tumors (Pinder et al 1994). Similarly, Hsp27-1 expression was found in various benign and malignant tissues, eg, in retinal neurons (Whitlock et al 2005a(Whitlock et al , 2005b, in reproductive tissues (White et al 2005), in normal and neoplastic renal tissue (Neuhofer et al 2005;Tremolada et al 2005), and in malignant thyroid tissue (Akslen and Varhaug 1995).…”
Section: Introductionmentioning
confidence: 98%